PERTANGGUNGJAWABAN PIDANA TERHADAP KORPORASI YANG MELAKUKAN TINDAK PIDANA LINGKUNGAN HIDUP - Siregar, Rian Angga Dinata; ', Firdaus; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corporate crime or White collar crime especially in environmental crime has its ownconstraints. Determining which board is responsible is quite difficult considering the complex formof management in a corporation. Therefore, there are doubts about the possibility of thecorporation to be liable for criminal responsibility and convicted. There are a number of views onthe criminal construction of a corporation so that it has implications for the difficulty ofdetermining corporate wrongdoing for criminal liability. The desire to ensnare corporationsinvolved in environmental crime cases is indeed not easy to realize. Although there is awarenessabout the importance of protecting the environment among law enforcement officials, the fact isthat it is not easy to ensnare perpetrators. Moreover, the majority of environmental criminaldefendants who were brought to court were either free or only sentenced to probation because ofthe difficulty of proving a mistake by a corporation.This research which is entitled